Randomized elimination and prolongation of ACE inhibitors and ARBs in coronavirus 2019 (REPLACE COVID) Trial Protocol. Issue 10 (16th September 2020) - Cohen, Jordana B.; Hanff, Thomas C.; Corrales‐Medina, Vicente; William, Preethi; Renna, Nicolas; Rosado‐Santander, Nelson R.; Rodriguez‐Mori, Juan E.; Spaak, Jonas; Andrade‐Villanueva, Jaime; Chang, Tara I.; Barbagelata, Alejandro; Alfonso, Carlos E.; et al.
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), the virus responsible for coronavirus disease 2019 (COVID‐19), is associated with high incidence of multiorgan dysfunction and death. Angiotensin‐converting enzyme 2 (ACE2), which facilitates SARS‐CoV‐2 host cell entry, may be impacted by angiotensin‐converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs), two commonly used antihypertensive classes. In a multicenter, international randomized controlled trial that began enrollment on March 31, 2020, participants are randomized to continuation vs withdrawal of their long‐term outpatient ACEI or ARB upon hospitalization with COVID‐19. The primary outcome is a hierarchical global rank score incorporating time to death, duration of mechanical ventilation, duration of renal replacement or vasopressor therapy, and multiorgan dysfunction severity. Approval for the study has been obtained from the Institutional Review Board of each participating institution, and all participants will provide informed consent. A data safety monitoring board has been assembled to provide independent oversight of the project.